Livelihood status and adaptation strategies of ethnic mountain households: Evidence from Sichuan, China - Sarker, Md Nazirul Islam; Li, Xiaohan; Lv, Yang; Pervez, A K M Kanak; Huq, Md Enamul (Journal of Social Economics Research, 2025)
Household livelihood assessment is an integral approach to determining the status of the development of rural people and society. Therefore, this study aims to explore the status of the livelihood and adaptation strategies of ethnic mountain people. A capital-based livelihood assessment was conducted on households living in Mount Qingcheng in Sichuan, China, under the guidance of the sustainable livelihood framework. Primary data were gathered through a semi-structured household survey of 42 ethnic mountain households complemented by two focus group discussions with community representatives. This study reveals that ethnic mountain households possess low levels of human capital (education, health, and vocational skills), limited natural capital (cultivable land and homestead areas), scarcity of physical capital (poor housing, production tools, vehicles, and durable assets), limited access to financial capital (income, borrowing informal and formal loans, and charity), and poor social capital (loose social networks within relatives, low opportunities for financial help, and job facilities). The analysis revealed a positive relationship between family size and household income, and cultivable land area. Cultivable land and homestead size are significantly positively related to dwelling quality (0.20*), financial security (0.60*), ease of obtaining informal loans (0.20*), and access to formal loans (0.30*). The major adaptation strategies depend on agriculture, off-farm income activities, social networks, traditional ecological knowledge (TEK), and migration for work. This study recommends that a continuous development program be implemented to help protect the culture and enhance the livelihood security of ethnic mountain people.